Frying Quality of Some Edible Oil Blends Based on Palm Olein - Shakak, Mahdi A. Saad; A, A. Haleem Raham; faki, Ahmed A. El (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Palm olein was blended with three Sudanese edible oils namely cottonseed,groundnut, and sunflower oils, at two levels (3:1; 1:1, respectively), exposure to fryingtemperature at 180 ± 20C for 5, 10 and 15hrs and acceptability tests of potato chips friedin such blends were carried out.In the acceptability tests, the sequence of preference of potato chips fried in palmolein blends showed that palm olein / sunflower oil (1:1; 3:1) blends, was similar to thepure palm olein in having first preference in color, flavor and taste, followed by chipsfried in palm olein / cottonseed oil blends, whereas the chips fried in palm olein /groundnut oil blends received the least acceptability.